QUO VADIS PONDOK PESANTREN DI ERA UNDANG-UNDANG PESANTREN - Jamal Mustofa; Marwan Salahuddin (IJoIS: Indonesian Journal of Islamic Studies, 2020)
This article aims to analyze the challenges of pesantren after the issuance of the pesantren law. Pesantren as an independent educational institution also plays three main functions, namely as an educational institution, a preaching institution and a community empowerment institution. Pesantren in a unique way and able to dialectic with the times and able to build a unique symbiosis with the state, but always with a careful character to the state. The presence of the Pesantren Law, on the one hand, is a class increase for pesantren, because it is recognized by the state as part of the national education system. However, a new challenge arises, namely in terms of how to maintain its distinctive character and freedom from state interference which tends to be hegemonic.